2017
DOI: 10.5114/aic.2017.66180
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous pulmonary valve implantation – state of the art and Polish experience

Abstract: Percutaneous pulmonary valve implantation (PPVI) is a relatively new method of treating patients with right ventricular outflow tract (RVOT) dysfunction after surgical repair of congenital heart disease. Since its introduction in 2000 by Bonhoeffer, more than ten thousand PPVI procedures have been performed worldwide. Indications for PPVI have been adapted from those accepted for surgical intervention. Two types of valves are being used: Melody Medtronic available in diameters 16 mm and 18 mm and the family of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 49 publications
0
20
0
3
Order By: Relevance
“…It is imperative to identify pre, intra, and postvalve implant factors that may identify those at the highest and lowest risk for the development of IE. Inadequate dental hygiene as well as lack of prophylaxis for dental and invasive procedures, intravenous therapy or drug use, piercings, tattoo, and nail biting are among some of the more established risk factors for IE as these practices facilitate the entry of bacteria into the bloodstream . Published studies have suggested that patients with non‐native RVOT anatomy, residual stenosis post‐TCPVR, those with prior history of endocarditis, and those that have undergone Melody™ jugular venous valve placement are at increased risk for the development of IE .…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative to identify pre, intra, and postvalve implant factors that may identify those at the highest and lowest risk for the development of IE. Inadequate dental hygiene as well as lack of prophylaxis for dental and invasive procedures, intravenous therapy or drug use, piercings, tattoo, and nail biting are among some of the more established risk factors for IE as these practices facilitate the entry of bacteria into the bloodstream . Published studies have suggested that patients with non‐native RVOT anatomy, residual stenosis post‐TCPVR, those with prior history of endocarditis, and those that have undergone Melody™ jugular venous valve placement are at increased risk for the development of IE .…”
Section: Discussionmentioning
confidence: 99%
“…Since the first PPVI by Bonhoeffer et al in 2000 , more than 10,000 procedures have been performed all around the world, with an increasing experience that has confirmed that PPVI is a valuable alternative to surgery . Being an interventional procedure, acute complications may occur and include coronary compression by the stent or the prosthesis, aortic root deformation, partial or total conduit rupture, guidewire related injuries of distal pulmonary artery branches, valve or stent migration, acute flash pulmonary oedema, and vascular access site damages .…”
Section: Introductionmentioning
confidence: 99%
“…PPVI is usually preceded by pre-stenting, especially when treating "native" RVOT dysfunction, in order to create an adequate landing zone for the valve. Different pre-stenting techniques can be adopted.They include the "Russian doll technique," the "jailing technique," the "Russian jailing technique," and the "telescopic technique" [5].Since the first PPVI by Bonhoeffer et al in 2000 [6], more than 10,000 procedures have been performed all around the world, with an increasing experience that has confirmed that PPVI is a valuable alternative to surgery [7]. Being an interventional procedure, acute complications may occur and include coronary compression by the stent or the prosthesis, aortic root deformation, partial or total conduit rupture, guidewire related injuries of distal pulmonary artery branches, valve or stent migration, acute flash pulmonary oedema, and vascular access site damages [8][9][10][11].Here, we report on a new complication that occurred in three of our patients undergoing Edwards-Sapien Valve implantation.…”
mentioning
confidence: 99%
“…For example, routine RVOT pre‐stenting, careful attention to any coronary artery compression, and strictly aseptic manipulations of the valved conduit have improved the outcomes. Studies have shown that PPVI is highly effective in reducing either stenosis or regurgitation of the RVOT . Although several studies have shown reductions in right ventricular dimensions, improvement of right ventricular function and patients’ functional capacity, the optimal timing for intervention remains under debate, particularly in patients with pure pulmonary regurgitation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that PPVI is highly effective in reducing either stenosis or regurgitation of the RVOT. [4][5][6][7][8][9][10][11][12][13][14] Although several studies have shown reductions in right ventricular dimensions, improvement of right ventricular function and patients' functional capacity, the optimal timing for intervention remains under debate, particularly in patients with pure pulmonary regurgitation. As data on efficacy and long-term clinical performance after PPVI is still limited, the aim of the present report was to evaluate indication, procedural success, complications, echocardio-…”
mentioning
confidence: 99%